Post-braze heat treatment of Inconel 718 alloy with BNi-2 filler metal - Chan, Chee Choong (2018)
Inconel 718 is a common material used in the aircraft industry such as in the turbine blades of an aircraft engine. They are subjected to extreme stresses constantly and therefore require regular maintenance for the engine to remain operational. Brazing is a repair process that fuses two metals by heating and melting a brazing alloy that bonds to the two pieces of parent meterial and joins them. However, brazing also induces undesirable mechanical properties on the brazed joints due to the high temperature of the brazing process. Thus, post weld heat treatment (PWHT) is used to recover and sometimes improve its mechanical properties. The aim of the project is to determine the most effective PWHT by analysing the microstructure, hardness, tensile properties and fractography of the Inconel 718 brazed joints using the BNi-2 filler metal. Scanning electron microscope (SEM) and electron backscatter diffraction (EBSD) system were used to study the fracture surfaces and phase composition respectively. Specimens underwent a combination of solution heat treatment at 980°C for 1 hour as well as aging at 760°C for 4 hours followed by 660°C for 4 hours. The purpose of aging is to precipitate strengthening γ´ and γ´´ phases, while solution heat treatment dissolves detrimental δ phase. Joints that were brazed had a brazing gap above the maximum brazing clearance (MBC) and so they fail at the joint centreline due to the formation of brittle eutectic phases. Hardness generally increased from the base metal to the filler metal. The hardest and strongest brazed joint was the specimen which underwent the solution strengthening and aging process. Future research can include the analysis of more mechanical properties in the selection of the most effective PWHT.